SPE India Oil and Gas Conference and Exhibition 1998
DOI: 10.2118/39509-ms
|View full text |Cite
|
Sign up to set email alerts
|

Multilaterals: An Overview and Issues Involved in Adopting This Technology

Abstract: Multilaterals, an upcoming technology, offers the potential for substantial improvement in well economics. Integrated efforts of service companies and operators have made this upcoming technology a viable completion technique. The issues like maturing reservoirs, many of the existing wells with uneconomical- to-recover results in place and increasingly expensive offshore structure and drilling operations, are addressed in a very positive way by recent advances in the ML Technology. This technology allows to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…5,6 This technology gap is significant for multilateral ER wells. 7,8 Previously, access to individual branches was not possible, 9,10 which prevented effective stimulation and production logging of individual laterals. Acid had to be bullheaded down wellbore tubulars or coiled tubing with the end of pipe near the lateral entrance.…”
Section: Spe 93500mentioning
confidence: 99%
“…5,6 This technology gap is significant for multilateral ER wells. 7,8 Previously, access to individual branches was not possible, 9,10 which prevented effective stimulation and production logging of individual laterals. Acid had to be bullheaded down wellbore tubulars or coiled tubing with the end of pipe near the lateral entrance.…”
Section: Spe 93500mentioning
confidence: 99%
“…Multilateral wellbores -separate drain holes or branches, drilled from a single primary borehole (Fraija et al, 2002) -offer the potential for substantial improvement in well economics (Vij et al, 1998). They potentially reduce total capital expenditures and development costs as well as operational expenses by decreasing the number of the required wells (Jordan et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This technology can help us to produce multiple reservoirs, enhance drainage pattern, increase fracture exposure, reduce environmental damage, reduce overburden and surface facilities costs, decrease impacts of water/gas coning, etc. (Vij et al, 1998;Garrouch et al, 2004). The current costs of drilling and completion of multidrain wells are more than several million dollars for each branch (Garrouch et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Salas et al (1996) identified eight categories of main potential applications of multilateral wells. Vij et al (1998) provided an overview of the multilateral technology and its limitations.…”
Section: Introductionmentioning
confidence: 99%